FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN MOLA HIDATIDOSA DI RSUP. DR. WAHIDIN SUDIROHUSODO MAKASSAR - Kasmiati (Stikes Graha Edukasi Makassar, 2021)
Objective: to determine the risk factors for age, parity, and previous pregnancy history of hydatidiform mole against the incidence of hydatidiform mole in RSUP. Dr. Wahidin Sudirohusodo Makassar. Method: analytic design with a case control study approach. The independent variables were age, parity, and previous molar pregnancy history. The population was all young pregnant bleeding. The number of sample cases and controls ratio 1: 1 is 38:38. The sampling technique was total sampling. Data were analyzed by univariate and bivariate. Result: odds ratio test with ? = 0.05. The results show that the age factor has (OR = 2.979) so that age has a 2.97 times risk of the incidence of hydatidiform mole, the parity factor has (OR = 4.431) so that parity has a risk of 4.4 times the incidence of hydatidiform mole, while a previous pregnancy history of hydatidiform mole are protective against the occurrence of hydatidiform mole. Conclusion: age and parity are risk factors for hydatidiform mole, while previous pregnancy history is only a protective factor against hydatidiform mole. Suggestion: health workers need to conduct socialization to prevent early marriage, promote family planning programs, programs for children at reproductive age, and remain vigilant about previous molar pregnancy history